Waste management accounting information system design at the Solusi Hijau Waste Bank - Rahmat Jatnika; Tety Elida Siregar (Jurnal Mantik, 2023)
The phenomena of establishing a circular economy is aggressively advocated both in Indonesia and globally as a step towards a new, greener model of economic transformation to lessen the impact on the environment and support long-term and sustainable economic growth. By 2025, the administration of JAKSTRANAS wants all waste to be controlled, a goal that will be aidsd by digitizing waste banks. The Solusi Hijau Waste Bank has not digitized its business processes, making it challenging for customers and collectors to obtain crucial information quickly, accurately, and in real time. This is why the research is urgent. This research object was to design a waste management accounting information system at the Solusi Hijau Waste Bank. The two stages of the research method are requirement analysis and system design, where the latter uses the Unified Modeling Language to model the process design. The conclusion of this research is that a waste management accounting information system for the Solusi Hijau Waste Bank has been successfully created. Process design, database design, and user interface design are all components of the system's design. The Solusi Hijau Waste Bank will hopefully be able to handle and obtain information about waste management, customer data, collector data, and transaction data conveniently, quickly, precisely, and in real time with the help of this system design. The Solusi Hijau Waste Bank is not the only waste bank that can use this system design; another waste bank that has roughly the same business procedures can as well